CARL SAGANS COSMIC CONNECTION: AN EXTRATERRESTRIAL PERSPECTIVE - SAGAN, CARL EDWARD, 1934-1996 (CAMBRIDGE CAMBRIDGE UNIVERSITY PRESS, 2000)
In 1973, Carl Sagan published The Cosmic Connection, a daring view of the universe, which rapidly became a classic work of popular science and inspired a generation of scientists and enthusiasts. This seminal work is reproduced here for a whole new generation to enjoy. In Sagan's typically lucid and lyrical style, he discusses many topics from astrophysics and solar system science, to colonization, terraforming and the search for extraterrestrials. Sagan conveys his own excitement and wonder, and relates the revelations of astronomy to the most profound human problems and concerns: issues that are just as valid today as they were thirty years ago. New to this edition are Freeman Dyson's comments on Sagan's vision and the importance of the work, Ann Druyan's assessment of Sagan's cultural significance as a champion of science, and David Morrison's discussion of the advances made since 1973 and what became of Sagan's predictions. Who knows what wonders this third millennium will reveal, but one thing is certain: Carl Sagan played a unique role in preparing us for them.
PORTUGUES
Keywords: EXTRATERRESTRES; VIDA EXTRATERRESTRE; ORIGEM DA VIDA; LIVRO